Le défi Charlie : les médias à l’épreuve des attentats - Vicky Girard (Communiquer)
Le défi Charlie: les médias à l’épreuve des attentats is a book of eleven contributions on the media coverage of the Charlie Hebdo attack. The forms of mediatization identified include complaints letters, political speeches and humorous programs. These various mediatizations were studied by the authors at different moments of the attack, at the time of the attack, during the march and during the debate. This book review discusses some of the collaborations by looking at some of the researchers’ interpretations, while highlighting the strengths and limitations of the work done.